Diaspora Arab dan Tionghoa dalam Surat Kabar Aljaum dan Keng Po Koleksi Perpustakaan Nasional Republik Indonesia - Frial Ramadhan Supratman (Institut Agama Islam Negeri Salatiga, 2022)
Diaspora problem is part of library studies which is interested to be researched. Indonesia is a state whose strategic place for diaspora community in the past. Arabs and Tionghoas diaspora were two diaspora communities which settled Indonesian regions. Study about diaspora does undoubtedly not received more attention yet from library studies perspective.Even though the research is highly important to enrich multidisciplinary aspect within library studies. The aim of this research analyzes information regarding Arabs and Tionghoa diaspora communities in rare newspaper collection of National Library of Indonesia. The result of this research is that the National Library deposits rare newspaper collection indicating the existence of diaspora communities globally. This research uses history approach on viewing newspaper as National Libraryof Indonesia’s collection. The conclusion of this research is that the National Library does not merely posses importance meaning for local community within scope of nation state, however, that for diaspora community in the global scale.